Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Given this recursive rule an = an-1 + 6
where your a1 = -13
find the next 4 terms in this sequence. Show your work


Sagot :

Step-by-step explanation:

a1 = -13

since an = an-1 + 6, we get

a2 = a1 + 6 = -13 + 6 = -7

a3 = a2 + 6 = -7 + 6 = -1

a4 = a3 + 6 = -1 + 6 = 5

a5 = a4 + 6 = 5 + 6 = 11